2020
DOI: 10.1016/j.intimp.2020.107065
|View full text |Cite
|
Sign up to set email alerts
|

Novel serological biomarkers for inflammation in predicting disease severity in patients with COVID-19

Abstract: Highlights: Patients with coronavirus disease 2019 (COVID-19) had altered inflammatory markers. High sensitivity C-reactive protein-(pre)albumin ratios positively correlated with severe COVID-19. Prognostic nutritional index negatively correlated with risk of severe COVID-19. Nomogram combining the three factors reliably predicted the progression of COVID-19. High sensitivity C-reactive protein-prealbumin and -albumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 41 publications
8
115
0
2
Order By: Relevance
“…Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 , 65 67 , 86 ]. Endpoints included disease severity based on current clinical guidelines (31 studies, 46%) [ 22 , 24 , 28 , 32 , 33 , 35 , 36 , 38 , 39 , 44 47 , 49 52 , 54 , 56 , 58 , 64 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 83 ], survival (19 studies, 28%) [ 20 , 23 , 26 , 30 , 31 , 34 , 42 , 53 , 59 – 62 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 , 65 67 , 86 ]. Endpoints included disease severity based on current clinical guidelines (31 studies, 46%) [ 22 , 24 , 28 , 32 , 33 , 35 , 36 , 38 , 39 , 44 47 , 49 52 , 54 , 56 , 58 , 64 , 66 , 69 , 72 , 73 , 75 , 77 , 79 , 81 83 ], survival (19 studies, 28%) [ 20 , 23 , 26 , 30 , 31 , 34 , 42 , 53 , 59 – 62 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…Overall, they included 4,616 COVID-19 patients, 3,502 (48% males, mean age 52 years) with low severity or who survived and 1,114 (61% males, mean age 64 years) with high severity or who died. Three studies were prospective ( 24 , 30 , 36 ),14 were retrospective ( 22 , 23 , 25 29 , 31 , 33 , 34 , 37 40 ), whereas the remaining two did not explicitly state the study design ( 32 , 35 ). Disease severity, based on current clinical guidelines, was assessed in 11 studies ( 22 , 23 , 25 , 28 , 30 , 33 , 35 , 37 40 ), prolonged viral clearance in two ( 26 , 36 ), transfer to ICU in one ( 29 ), survival in three ( 27 , 31 , 32 ), presence of acute respiratory distress syndrome in one ( 34 ), and multiple end points in one ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that lower PNI was correlated with a lower survival rate in patients having various malignancies, such as esophageal squamous cancer, colorectal cancer, gastric cancer, and lung cancer [30,31,32]. Nowadays, PNI is an important biomarker that can be used to discriminate COVID-19 severity, according to the results of several studies [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%